Gender and rural globalization international perspectives on gender and rural development - Bock, Bettina B. (Bettina Barbara), 1960- (CABI, 2017)
This book explores how rural gender relations are changing in a globalizing world and how they fundamentally impact the structure of agricultural life in rural areas and urban-rural relations. It analyzes the development of rural gender relations in specific places around the world and looks into the effects of the increasing connectivity and mobility of people across places. The themes covered are: gender and mobility, gender and agriculture, gender and rural politics, rurality and gender identity, and women and international development. Each theme has an overview of the state of the art in that specific thematic area and integrates relevant case studies.